The Role of Virtual Laboratories in Reducing Students’ Anxiety within Physics Education: A Literature Review - Erma Fitriyana; Mirna Wahdaniyati; Eka Puji Astuti (Indonesian, 2023)
Physics learning ideally emphasizes direct experience through practicum activities, yet its implementation often faces constraints related to facilities, time, equipment, and laboratory access. These limitations may affect conceptual understanding and learning outcomes and may also increase students’ anxiety when they face abstract concepts or real laboratory procedures. This study aims to analyze the role of virtual laboratories in reducing students’ anxiety in physics learning through a descriptive qualitative literature review. Data were collected from eight relevant open-access journal articles published between 2014 and 2023 and obtained from Google Scholar, GARUDA, and university journal portals. The articles were reviewed based on their focus, education level, method, and main findings. The analysis focused on problems in physics learning, the effectiveness of virtual laboratories, and their potential contribution to reducing learning anxiety. The findings indicate that virtual laboratories, particularly PhET-based simulations, support conceptual understanding, learning outcomes, motivation, learning experience, and higher-order thinking skills. Virtual laboratories also provide a safer, more flexible, and repeatable learning environment, which may indirectly reduce anxiety by increasing self-confidence and engagement. However, direct empirical evidence on anxiety reduction remains limited, so further experimental studies are needed.